INVESTMENT IN PORT INFRASTRUCTURE: Transparency in the origin and application of resources - study of the Port of Santos - Lopes Pereira, Camila (2022)
Investment in the port infrastructure at the Port of Santos is carried out by the Company of the State of São Paulo by means of the proceeds from its revenues and the contributions of capital consigned by the Federal Government through the increase of capital by the National Treasury. The decision on the investments to be made is based on public policies, guided by the Pluriannual Plan of the Union and provided for in the Annual Budget Law. All the dynamics are the result of a complex process of difficult verification and understanding, making the transparency of government actions noisy.